Progressive corporate governance for the 21st century - Talbot, Lorraine (Abingdon, Oxon : Routledge, 2013)
'This book provides a critical and comparative approach to corporate governance. The book sets out, and makes a case for what the author terms'progressive corporate governance', in order to promote an approach to corporations which furthers social progress. The book takes a hybrid approach in order to bridge the gap between theory and practice, and assesses the situation in Anglo-American, European and transitional economies. The book argues that in judging which governance theories and practices are progressive one must consider them in historical and social context and it also considers whether there are some governance approaches which may be said to be universally progressive. The book looks at progressive corporate governance in the light of the recent worldwide economic crises and explores how state intervention should proceed.'--
'Progressive Corporate Governance for the 21st Century is a wide ranging and ambitious study of why corporate governance is in the shape that it is, and how it can be improved. The book sets out the emergence of a shareholder primacy orientated corporate governance using a study of historical development in the United Kingdom and the United States. Talbot sees shareholder primacy as a political choice made by governments, not a'natural' feature of the inevitable market. She describes the periods of progressive corporate governance which governments adopted in the middle of the twentieth century with a close examination of the theories of the company which then prevailed. She critically examines the rise of neoliberal theories on the company and corporate governance and argues that their approach and impact is socially regressive. In examining contemporary corporate governance she shows how the form of governance, as informed and described by prevailing regulatory theories, enables neoliberal outcomes. She illustrates how United Kingdom-derived corporate governance codes have had global influence, constructing the corporate governance initiatives of European and global institutions. She argues that the form of the Codes enables a neoliberal agenda to proliferate with negative social consequences. After illustrating how ex-command economies were earlier subjected to failed and destructive neoliberal proscriptions for transition she shows how neoliberalism has re-entered these economies through United Kingdom and OECD inspired corporate governance Codes. The book concludes with suggestions for new approaches which would make the company work for the people, rather than the shareholder'--
Introduction : progressive corporate governance : what it is and what it isn't? -- Progressive thought and the historical emergence of the company in England 1770-1900 -- Corporate governance in the United Kingdom in the 20th century : including a period of progressive governance -- The United States and progressive governance : the historical development of the American corporation 1790-1944 -- The managerialists' progressive corporation and the rise of neoliberal corporate governance -- The retreat from progress : modern corporate governance, substance and form -- The march to anti-progressiveness : neoliberalism and transition economies.
Includes bibliographical references and indexes.
Keywords: Corporate governance -- Law and legislation -- United Kingdom; Corporate governance -- Law and legislation -- United States; Corporate governance -- Political aspects